2015
DOI: 10.1002/qua.25022
|View full text |Cite
|
Sign up to set email alerts
|

H‐bond and electric field correlations for water in highly hydrated crystals

Abstract: We present periodic plane‐wave density functional theory (DFT) Perdew–Burke–Ernzerhof (PBE‐D2) calculations for four highly hydrated crystals, Na2CO3·10H2O, MgSO4·7H2O, MgSO4·11H2O, and Al(NO3)3·9H2O, containing 37 structurally unique water molecules and 74 unique hydrogen bonds. The calculated R(H···O) distances lie in the range 1.60–2.05 Å, the anharmonic OH frequencies in the range 2570–3425 cm−1, and the water dipole moments lie in the range 2.9–4.3 Debye, as calculated from the Wannier function centers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 75 publications
1
14
0
Order By: Relevance
“…On average the water molecule is thus enhanced by a factor of more than 60% compared to the gas-phase value. This is a large increase, but much smaller than what has been shown to occur in simple ionic crystalline hydrates which can display Wannier-type water dipole moments well over 4 Debye [64][65].…”
Section: Molecular Dipole Momentmentioning
confidence: 66%
“…On average the water molecule is thus enhanced by a factor of more than 60% compared to the gas-phase value. This is a large increase, but much smaller than what has been shown to occur in simple ionic crystalline hydrates which can display Wannier-type water dipole moments well over 4 Debye [64][65].…”
Section: Molecular Dipole Momentmentioning
confidence: 66%
“…The slab parameters are fixed, and structural relaxations are limited to the positional parameters of atoms. This is a typical approximation for the calculation of the molecular crystals and periodic systems with H‐bonds, since the change in the volume of a simulated cell appears to be insignificant after the full optimization of molecular crystals . BSSE‐corrected interaction energies between H 2 O/H 2 O 2 molecules and slabs were determined using the counterpoise method as implemented in the CRYSTAL09 suite.…”
Section: Methodsmentioning
confidence: 99%
“…The reason behind these systematic experimental distance "errors" is known and was elaborated on in Ref. 6. The resulting 'r(OH) vs. R(O•••O)' correlation curve from the quantum-mechanical crystal calculations is shown in Figure 3c.…”
Section: Water In Crystalline Hydratesmentioning
confidence: 90%
“…We have found that theoretical calculations for ionic hydrate crystals present a unique opportunity to gather novel information about the water molecule and its structure-property relations [6]. Ample high-quality structural data are available from diffraction experiments for a large number of crystalline hydrates where water coexists with metal ions, sulphates, nitrates, halides etc., and we, the modelers, can then focus on modelling the properties themselves.…”
Section: Water In Crystalline Hydratesmentioning
confidence: 99%
See 1 more Smart Citation